Selective Functionalization of Aminoheterocycles by a Pyrylium Salt. Issue 34 (20th July 2018) - Moser, Daniel; Duan, Yaya; Wang, Feng; Ma, Yuanhong; O'Neill, Matthew J.; Cornella, Josep
Abstract: The functionalization of aminoheterocycles by using a pyrylium tetrafluoroborate reagent (Pyry‐BF4 ) is presented. This reagent efficiently condenses with a great variety of heterocyclic amines and primes the C−N bond for nucleophilic aromatic substitution. More than 60 examples for the formation of C−O, C−N, C−S, or C−SO2 R bonds are disclosed herein. In contrast to C−N activation through diazotization and polyalkylation, this method is characterized by its mild conditions and impressive functional‐group tolerance. In addition to small‐molecule derivatization, Pyry‐BF4 allows the introduction of functional groups in a late‐stage fashion to furnish highly functionalized structures. Abstract : Never too late : Pyry‐BF4 was identified as a broadly useful reagent for the activation of heteroaromatic amines and subsequent functionalization to forge C−N, C−O, and C−S bonds. The transformation displays remarkable chemoselectivity, which makes it suitable for use in late‐stage functionalization. PST=pyridine sulfur trioxide.